A gathering of heroes reflections on rage and responsibility ; a memoir of the Los Angeles riots - Alan-Williams, Gregory (Academy Chicago Publ., 1994)
On April 29, 1992, actor Gregory Alan Williams walked into the intersection of Florence and Normandie avenues - in the heart of South Central Los Angeles - and into the midst of the worst riot in America's recent history. Summoning a courage born from the examples of his own personal heroes, Williams, an African American, rescued Japanese motorist Takao Hirata from an angry mob armed with bottles and metal rods. Through an endless shower of projectiles and verbal abuse
Keywords: Alan-Williams, Gregory; Geschichte 1900-2000; Geschichte 1992; Geschichte; Racism -- California -- Los Angeles; Riots -- California -- Los Angeles -- History -- 20th century; Violence -- California -- Los Angeles -- History -- 20th century; Rassenunruhen; Los Angeles (Calif.) -- Race relations; Los Angeles, Calif.; Erlebnisbericht